The Effect Of Using The Napier Rod Props On The Mathematics Learning Outcomes Of Class IV Student’s Of Elementary School - A. Dwi Andrillah; Sayidiman Sayidiman; Nurhaedah Nurhaedah (International Journal of Elementary School Teacher, 2022)
The research problem in this study is the low results of mathematics learning. This study aims to find out an overview of the use of napier rod props in mathematics subjects of grade IV students of UPT SPF SDN Maccini II Makassar City, to find out an overview of students' mathematics learning outcomes after using napier stem props in class IV UPT SPF SDN Maccini II Makassar City, and to find out the influence of the use of napier rod props on the results of learning mathematics for grade IV students of upt spf sdn Maccini II Makassar City. This research uses a quantitative approach with an experimental type of research. The research design used in this study is quasi experimental group design with the form of nonequivalent control group design which is carried out in two classes, namely the experimental class and the control class with stages of activity including giving pretests, giving treatment in experimental classes and giving posttests. Data collection techniques are in the form of tests, observations, and documentation. The population in this study was all grade IV students of UPT SPF SDN Maccini II Makassar City. The sample in this study was 54 students consisting of 27 class IV A students and 27 class IV B students. The data analysis techniques used in this study are descriptive statistical analysis and inferential statistical analysis. The results of this study showed that (1) The use of the napier rod teaching aid in the learning process of the experimental class in mathematics class IV UPT SPF SDN Macini II Makassar City went very well. (2) Student learning outcomes in the experimental class are more improved than learning outcomes in the control class. This is evidenced by the learning outcomes in the experimental class which are in the good category, while the learning outcomes in the control class are only in the sufficient category. (3) There is an effect of using the napier rod teaching aid on learning outcomes in mathematics class IV UPT SPF SDN Maccini II Makassar City.